An Evaluation of Security Standards Implementation in Quantum Key Distribution Systems. Issue 1 (June 2013) - Harper, Carole; Grimaila, Michael R.; Baumgartner, Gerald
Abstract: Quantum Key Distribution (QKD) systems combine cryptographic primitives with quantum information theory to produce a theoretic unconditionally secure cryptographic key. However, real‐world implementations of QKD systems are far from ideal and significantly differ from the theoretic models. Because of this real‐world QKD systems require additional practical considerations when implemented to achieve secure operations. In this paper, a content analysis of the published literature is conducted to determine if established security and cryptographic standards are addressed in real world, practical QKD implementations. The research reveals that a majority of real world QKD implementations examined do not take advantage of established security and cryptographic standards. Based upon an analysis of existing industry security and cryptographic standards and best practices, systems architecture guidelines are used to make recommendations for how these standards can and should be applied to establish a practical, secure, QKD system framework.